2016
DOI: 10.1590/bjpt-rbf.2014.0160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 10,000 steps a day on physical and mental health in overweight participants in a community setting: a preliminary study

Abstract: BackgroundBeing overweight is associated not only with physical health problems, but also with risk of mental health problems. Increased physical activity (PA) has been recommended for the prevention of cardiovascular disease; however, little is known about the effect of walking on physical and mental health outcomes.ObjectiveThe purpose of the study was to explore the effectiveness of a pedometer-based PA intervention on physical and mental health states.MethodThirty-five overweight participants with body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 23 publications
0
20
0
3
Order By: Relevance
“…Increased physical activity can lead to better physical and mental outcomes [23][24][25][26] , and level of physical activity can serve as a useful measure of overall health 27 . Postoperative mobility has long been touted as a reliable indicator of surgical recovery and good post-operative prognosis 2,3,6,7,14,[28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Increased physical activity can lead to better physical and mental outcomes [23][24][25][26] , and level of physical activity can serve as a useful measure of overall health 27 . Postoperative mobility has long been touted as a reliable indicator of surgical recovery and good post-operative prognosis 2,3,6,7,14,[28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a body of evidence supporting that increased physical activity is associated with decreased depressive symptoms and mental health problems. 8 , 32 - 34 …”
Section: Discussionmentioning
confidence: 99%
“… 5 - 7 In addition, symptoms of depression have also been negatively associated with physical activity level. 8 Furthermore, a number of studies have revealed that older adults with low physical activity exhibited a high level of depression. 9 - 11 However, little is known regarding the differences in depression and physical activity between older adults with and without cognitive impairment.…”
mentioning
confidence: 99%
“…I mírná tělesná aktivita, jako je chůze, zlepšuje emoční stav (Sakuragi a Sugiyama, 2006, Yuenyongchaiwat, 2016. Hněv a nadměrná fyzická aktivita zvyšují riziko srdeční příhody (Smyth a spol., 2016) a lze předpokládat, že kombinace obou těchto faktorů riziko ještě zvýší.…”
Section: Tělesná Aktivita a Jiné Emoceunclassified